Interactive Digital Comic Teaching Materials to Increase Student Engagement and Learning Outcomes - Khotimah, Husnul; Hidayat, Nandang (Universitas Pendidikan Ganesha, 2022)
The digital era and the internet of things have had an impact on interaction patterns in learning activities. Online learning and teaching materials packaged in digital form have become a necessity. Teachers at the elementary school level are generally not ready for the demands of these changes, especially in developing digital teaching materials. This study aims to increase student involvement in the online independent learning process and learning outcomes by using interactive digital comics teaching materials. The research method used is the ADDIE model development research method (Analyze, Design, Develop, Implement, and Evaluate). This study involved 1373 students, 8 principals, and 20 teachers from 9 elementary schools who were selected as the pilot site in Tapos District, Depok City, West Java. Data was collected using instruments in the form of learning outcomes tests and questionnaires for students, teachers, and parents sent via a google form link. The data analysis technique used descriptive statistical analysis and inferential statistics, namely one-way ANOVA. This study concludes that the use of teaching materials packaged in the form of interactive digital comics with the theme “Movement Organs of Animals and Humans” sub-theme “Humans and the environment” has been proven to be effective in increasing the intensity of student involvement in online independent learning and the achievement of learning outcomes. The implication of the results of this study is that interactive digital comics are recommended for use in online independent learning for elementary school students.